SF3B1, NRAS, KIT, and BRAF Mutation; CD117 and cMYC Expression; and Tumoral Pigmentation in Sinonasal Melanomas: An Analysis With Newly Found Molecular Alterations and Some Population-Based Molecular Differences. (February 2019) - Wroblewska, Joanna P.; Mull, Jason; Wu, Cheng-Lin; Fujimoto, Masakazu; Ogawa, Toru; Marszalek, Andrzej; Hoang, Mai P.
Abstract : Sinonasal melanomas encompass melanoma arising in the nasal cavity and paranasal sinuses. Despite recent advances in tumor genomics, correlation between mutational status and protein expression with prognosis and tumor pigmentation has not been carried out in sinonasal melanomas. Ninety-five sinonasal melanomas from 95 patients were included. As per univariate analyses, age was the only variable that significantly correlated with progression-free survival. SF3B1, NRAS, KIT, and BRAF mutations were documented in 7% (5/72), 22% (16/72), 22% (16/72), and 8% (6/72) of cases, respectively. Comutation was detected in 6 cases: NRAS and KIT in 2 cases; NRAS and BRAF in 2 cases; SF3B1, KIT, and BRAF in one case; and SF3B1, NRAS, and KIT in one case. Correlations approaching statistical significance were observed between BRAF mutation status and poorer overall survival and progression-free survival (log-rank P -values=0.054 and 0.061). Increased CD117 expression (33%, 29/88) and decreased nuclear cMYC expression (40%, 39/84) significantly correlated with cytoplasmic pigmentation. Several SF3B1, NRAS, and KIT mutations not previously documented in sinonasal melanomas were detected in our series, suggesting a potential role for targeted therapies. A similar frequency of SF3B1, NRAS, and KIT mutations was noted in Asian cases, whereas NRAS, KIT, and BRAF mutations were predominant in the United States and European cases; however, the number of included cases was small. The significant association between CD117 and cMYC expression with increased cytoplasmic pigmentation in our series suggests that the pigmented morphologic appearance of sinonasal melanomas could be attributed to the underlying oncogenic mutations and metabolic interaction.